Chronic care model and cost reduction in initial health: a new approach for satisfaction and improvement of chronicity - Stefano Marcelli; Chiara Gatti; Renato Rocchi; Silvano Troiani; Sandro Di Tuccio; Cinzia Giuli; Demetrio Postacchini; Adoriano Santarelli (Geriatric Care, 2017)
Nowadays, the number of elderly is growing, with consequent increase of chronic diseases. An effective approach to reduce the costs incurred is required. The Chronic Care Model has proven to be a good starting point for a better management of economic and human resources.